The fall and rise of King Oedipus: On sacrificial logic and "Proto-Christology" - Delport, Khegan (Stellenbosch Theological Journal, 2021)
This essay is placed within a continuing debate on the appropriateness of a Christian deployment of tragedy. According David Bentley Hart, tragedy legitimates a sacrificial and scapegoating logic that is in contradiction with the Christian gospel. It promotes exclusion and therefore is imaginatively and metaphysically conservative in its import. In the ensuing argument, I hope to show through one example how even Greek tragedy can resist some of these claims. Drawing on the seminal work of Jean-Pierre Vernant and Pierre Vidal-Naquet, I argue that Sophocles' Oedipus cycle, firstly, demonstrates the inability of nomos to grasp the exception of Oedipus, and that this might constitute a critique rather than a simple legitimation of the civic order. Secondly, the narrative arc of Oedipus Tyrannus and Oedipus at Colonus point towards incorporation rather than final exclusion, and that his apotheosis could be read as resisting deleterious tropes of a final holocaust of the tragic figure. In the final section, drawing on Rowan Williams, I discuss the problems associated with literary Christologies in general, and whether it could be theologically feasible to talk about the Theban cycle as exhibiting a "Proto-Christology".